LEBANESE EMIGRANTS: CROSS-CULTURAL VECTORS - Akl M. Kairouz; Issam Y. Atala (European Scientific Journal, ESJ, 2014)
Lebanese Emigrants: Cross-cultural Vectors Unlimited technological discoveries and innovations, globalization, cross-cultural paradigms, wars, international communication and interdependency have contributed to unprecedented worldwide human mobility through emigration. Lebanon was highly affected, for the number of its emigrant citizens to foreign countries exceeds 3 times those still residing in the home country. The 14 million Lebanese emigrants are settled all over the world in search of economic, health and personal security. The official Lebanese policy today focuses upon establishing bonds with the emigrants, based on the importance of having them liaise with their country of origin on the socio-economic and political levels. These emigrants acted as transporters of Lebanese culture into the world and in return carry foreign culture into Lebanon. The research concentrates upon the role of international cultural trends over the Lebanese youth. It also offers recommendations to effectively deal with this issue for the mutual benefits of both the resident and emigrant Lebanon.